RELATIONSHIP AMONG INFORMATION EXPOSURE, PERCEPTION, ATTITUDES, AND TRENDS IN ELECTRONIC CIGARETTE SMOKING BEHAVIORS IN SECONDARY SCHOOL STUDENTS - Mungmai , Arrak; Rodpipat, Sarinya; Sarayuthpitak, Jintana (Academic Journal of Thailand National Sports University, 2023)
The trend of using e-cigarettes is widespread in Thai society. In particular, there is a tendency to use it more highly among teenagers. There is a common misconception that e - cigarettes are safer than conventional cigarettes. This research was a cross - sectional analytical study with two objectives: 1) to study the level of Information exposure, perceptions, attitudes, and trends in e - cigarette smoking behavior among secondary school students, 2) to study the correlation between information exposure, perceptions, attitudes, and trends in e - cigarette smoking behavior among secondary school students. The 600 samples of high school students in the Bangkok Metropolis were obtained by multi - stage sampling. The research instrument was online questionnaires. The data were analyzed using frequency distribution, percentage, mean and standard deviation, and Pearson’s Correlation Coefficient statistics. The results of the research were as follows: 1) The information about e - cigarettes was at the low level, awareness about e - cigarettes and attitudes towards e - cigarettes were in the moderate level, and trends in e - cigarette smoking behavior was at a high level. The students received information about e - cigarettes from family does friends. The issue that most recognized was that e - cigarettes didn’t contain cancer - causing substances. The most attitudinal point was that I thought e - cigarette smoking made it acceptable, and the most smoking e - cigarette behaviors were that they, students smoked e - cigarettes more than 7 times / week. 2) The results of correlation between trends in e - cigarette smoking behavior; it was found that information exposure was negatively correlated with a high magnitude (r = - 0.12), There was no correlation in perceptions (r = 0.00), and attitudes of high school students were positively correlated (r = 0.65). It was concluded that news exposure and attitude were related to e - cigarette smoking behavior tendency and perception was not correlated with statistically significant exposure at 0.05.